2022
DOI: 10.1038/s41467-022-31021-z
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution two-dimensional electronic spectroscopy reveals the homogeneous line profile of chromophores solvated in nanoclusters

Abstract: Doped clusters in the gas phase provide nanoconfined model systems for the study of system-bath interactions. To gain insight into interaction mechanisms between chromophores and their environment, the ensemble inhomogeneity has to be lifted and the homogeneous line profile must be accessed. However, such measurements are very challenging at the low particle densities and low signal levels in cluster beam experiments. Here, we dope cryogenic rare-gas clusters with phthalocyanine molecules and apply action-dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…In addition, 2DES allows to separate the homogeneous and inhomogeneous broadening. [ 24 ] Furthermore, since the method probes the third‐order nonlinear response, the spectral features are narrower than what they are in linear spectroscopy because all line‐shapes are narrowed by any additional order.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 2DES allows to separate the homogeneous and inhomogeneous broadening. [ 24 ] Furthermore, since the method probes the third‐order nonlinear response, the spectral features are narrower than what they are in linear spectroscopy because all line‐shapes are narrowed by any additional order.…”
Section: Introductionmentioning
confidence: 99%
“…The cold and controlled conditions provided by superfluid helium nanodroplets (He N ) enable the preparation of a wide range of otherwise inaccessible systems, as demonstrated by over three decades of frequency-domain spectroscopy 12 and mass spectrometry. 13 Concerning time-domain studies, the opportunities of He N are currently being explored and a number of photoinduced processes could be identified and characterized, including, among others, molecular alignment, 14 coherent nuclear vibration, 15–17 bond formation, 18 solvent dynamics following electronic excitation, 19–22 internal conversion, 23 quantum beats, 24 intermolecular energy transfer, 25 or nanoplasma formation. 26,27 These seminal studies have shown that, for pump–probe photoionization, the electron kinetic energy can be used as an accurate observable for processes inside He N because the helium-influence on free electrons through binary collisions is sufficiently low.…”
Section: Introductionmentioning
confidence: 99%
“…To separate these contributions, the phases of the laser pulses are manipulated through either phase-cycling , or phase-modulation schemes. Depending on the nature of the incoherent signal, different detection schemes have been implemented based on measuring fluorescence, photocurrent, photoions, and photoelectrons, paving the way for studying systems in operando conditions. , Furthermore, the combination of A-2DES with microscopy and single-molecule , techniques allows to go beyond the diffraction limit, thus circumventing the effects of inhomogeneous disorder.…”
mentioning
confidence: 99%